Cuttlefish Sepia officinalis Preferentially Respond to Bottom Rather than Side Stimuli When Not Allowed Adjacent to Tank Walls - Taniguchi, Darcy A. A.; Gagnon, Yakir; Wheeler, Benjamin R.; Johnsen, Sönke; Jaffe, Jules S. (PLOS ONE, 2015)
Cuttlefish are cephalopods capable of rapid camouflage responses to visual stimuli. However, it is not always clear to what these animals are responding. Previous studies have found cuttlefish to be more responsive to lateral stimuli rather than substrate. However, in previous works, the cuttlefish were allowed to settle next to the lateral stimuli. In this study, we examine whether juvenile cuttlefish (Sepia officinalis) respond more strongly to visual stimuli seen on the sides versus the bottom of an experimental aquarium, specifically when the animals are not allowed to be adjacent to the tank walls. We used the Sub Sea Holodeck, a novel aquarium that employs plasma display screens to create a variety of artificial visual environments without disturbing the animals. Once the cuttlefish were acclimated, we compared the variability of camouflage patterns that were elicited from displaying various stimuli on the bottom versus the sides of the Holodeck. To characterize the camouflage patterns, we classified them in terms of uniform, disruptive, and mottled patterning. The elicited camouflage patterns from different bottom stimuli were more variable than those elicited by different side stimuli, suggesting that S. officinalis responds more strongly to the patterns displayed on the bottom than the sides of the tank. We argue that the cuttlefish pay more attention to the bottom of the Holodeck because it is closer and thus more relevant for camouflage.